Large Eddy Simulation of a Steady Circular Jet Issuing into Quiescent Fluid - Jewkes, James; King, Andrew; Chung, Y. (Modelling and Simulation Society of Australia and New Zealand, 2011)
In this paper we present preliminary results from a high-resolution large eddy simulation (LES) study which will establish whether jet inlet velocity conditions are of significance in separation control applications. We include orifice geometry, in order to allow realistic turbulent structures to naturally develop. Ultimately, we will simulate various momentum thicknesses, (D/0 = 50, 80, 120 and 180)at Rej = 104 where Rej = UjD/v, where Uj is the jet inflow velocity and D is the jet diameter, however this paper presents initial high-resolution LES results for a steady jet, Rej = 104, D/0 = 50. The ~ 1:2 x 107 cell model was computed using the iVEC EPIC supercomputing cluster, and our local Beowulf cluster at Curtin University, (12 Intel i7 920 quad core CPUs (= 48 cores)). Our results show promising agreement with validation data, and indicate that our model has the potential to produce useful and accurate data regarding the evolution of a steady turbulent jet issuing into quiescent air.